A Schematic Review on Machine Learning Techniques and Its Importance in The Present Scenario - Swapnaja More (AG Volumes, 2022)
Machine learning is a dynamic area in the research as well as industry, with innovative techniques created all time. The pace and intricacy of the industry makes keeping up with the new tactics challenging even for specialists — and possibly daunting for newcomers. The objective of the subject is learning, that is, gaining skills or information through experience. Most typically, this implies synthesizing meaningful ideas from past facts. As such, there are many distinct forms of learning which you may face as a practitioner in the area of machine learning: from complete fields of research to individual methodologies. This paper reviews several techniques and algorithm that has been done in the field of machine learning along with their applications in different environments.